Pożegnanie z imperium? Użyteczność teorii postkolonialnej w badaniach nad współczesną ukraińską prozą kobiecą - Radecka, Aniela (Slavia Occidentalis, 2016)
Farewell to Empire is not a one-off act but an extremely complex process that has lasted many years. The decolonisation and de-Sovietisation of Ukrainian society is possible only by overcoming the mental effects of colonialism. Existence from revolution to revolution, and in consequence from revolution to war, was an experience shared by at least three generations of Ukrainian writers. However, each generation has either had different experiences with the previous political system, or none at all. Yet their lives are now connected with it through the experiences of previous generations. In the case of the contemporary analysis of Ukrainian women’s prose, the postcolonial perspective, combined with gender studies and a feminist critique, provides an extensive theoretical background for distinguishing the consequences of colonial/totalitarian practices and resistance strategies. In these narratives, women are the subjects and they speak in their own names. By analysing the literary representations of female figures who have contributed to the literary development of the independent state since the 1990s, the women can recreate their roles in creating modern Ukrainian statehood, shaping an independent society, or, on a micro scale, recreating their path to (re)constructing their own identity.